DAMPAK MUSIM PENANGKAPAN TERHADAP POPULASI RAJUNGAN DAN EKOSISTEM DI PERAIRAN SEGERI KABUPATEN PANGKEP - Tajuddin, Mustamin; Wamnebo, muhammad Ikhsan; Randi, Randi (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
Pangkep Regency has great fisheries and fisheries potential, including the potential for crab resources to be used responsibly. The crab fishing season has a significant impact on crab populations and the ecosystem of Segeri's waters. SeIama capture season. The objectives of the research that will be carried out are 1) to analyze the seasonal effects of crab fishing, 2) to assess the impact of the fishing season on crab populations, 3) to explore the effects of the fishing season on the ecosystem. Method of Determination of the fishing season with the criteria is if the seasonal index is more than 1 (more than 100 %) or above the average, and not the season if the seasonal index is less than 1 (less than 100 %). If IM = 1 (100 %), this value is equal to the monthly average price so it can be said to be normal or balanced. The mapping of fishing areas (rajungan) is carried out partifively through the geographic information system (GIS). The peak yield of the crab fishing season occurs in July and November. The average weight of crabs obtained using dragon bubu and gill net is 1.91 kg and 3.43 kg. Intensive fishing activities can cause turbidity due to sediment stirring on the seafloor and affect seagrass and algae that function as feeding grounds and nursery grounds.